(untitled) (Journal of Student Affairs in Africa, 2021)
The International Association of Student Affairs and Services (IASAS) and NASPA Student Affairs Administrators in Higher Education have collaborated over the past decade on a biennial basis, sponsoring the Global Summit on Student Affairs and Services. In the past, the Summit has taken place in Washington, D.C.; Rome, Italy; and Cape Town, South Africa.